Agrarian Distress and Farmers’ Suicides in Karnataka: Strategy for Prevention - Gyanappa Huddar, *Purnanand Nagappa Sangalad, Malakajappa (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Agriculture is a largest economic sector and plays a significant role in the overall socio economic development of our country. More than 80 percent of the farmers working in this sector are marginal and small-scale farmers. They depend on loan from private money lenders or from financial institutions for the cultivation of their land. They depend on agricultural income for their family expenses, education and marriage of the children. The agriculture in India is in crises and farmers of various states Karnataka in particular are in distress due to indebtedness, repeated failure of crops, increasing cost of production, poor quality of seeds, impact of globalization, exploitation by money lenders and businessmen and the other factors are the main causes for their distress which lead to suicides. Various steps have been taken by the Union and the State Governments by giving concessions to farming community. The Union Government has waived of the loan of marginal and small –scale farmers, steps have taken to supply fertilizers at highly subsidized rates. The State Government has given the loan facility at 3 percent interest. Free supply of electricity is given to the farmers pump sets. All these measures have helped farmers to some extent. In spite of the various measures taken by Central and the State Governments the suicide by farmers is still continued. The concerted efforts are to be made by all those concerned to bring happiness on the face of the farmers.